Towards understanding the effect of cedar roof covering application on firebrand production in large outdoor fires - Suzuki, Sayaka (J Clean Prod, 2021)
Due to the increased concern for the environment, sustainable construction materials are getting increased attention. Wood is considered a renewable, sustainable construction material. The problem with wood is that it is a fire-prone material. With an increasing number of wildland-urban interface (WUI) fires recently, it is important to consider that wood buildings are in danger to be ignited as well as may produce new sources of ignition due to firebrand production. Experiments were performed to investigate cedar roof covering effects of firebrand production from roof assemblies. Two wind speeds, 6 m/s and 8 m/s were selected for this experiment for a comparison with literature. The wood materials used were untreated cedar shingles, untreated cedar shakes, fire retardant cedar shingles and fire retardant cedar shakes. The roof assembly with fire retardant cedar shakes applied produced little or no firebrands under both wind speeds tested. Roof coverings fitted with cedar siding produced more variety of firebrands compared to only base sheathing materials. The mass and the projected area of firebrands were found to have a linear relationship. The firebrand coefficient was used for comparison. With attendant increase in wind speed, the firebrand coefficient increased in this study.